Air quality study in Pasir Gudang industrial, commercial and residential areas - Mohd. Yusof, Mohd. Badruddin; Yusof, Norazrina (Faculty of Civil Engineering, 2007)
Pasir Gudang is well-known for its industrial activities in the State of Johore, which contribute to air quality problems in the surrounding areas. A study was carried out around the Pasir Gudang areas, particularly the Town Centre Planning Block (BP1) as well as Industrial and Ports Planning Block (BP2). Five sampling stations were selected which include two in the industrial areas(Jalan Emas 2 and Jalan Keluli 3 Stations), two in the residential (Taman Mawar and Taman Air Biru Stations) and another in the commercial area (Kompleks Perbandaran Pasir Gudang Station). The parameters involved in the data collection stage include CO, NO2, SO2, O3, and temperature. These readings were recorded for twelve hours from 0800 until 2000 hours during both weekdays and weekends, using GrayWolf DirectSense TOX PPC Kit. The data collected are then analysed in the graphic form in order to obtain the trend of the gases concentration with time, types of land use and temperature. Based on the results obtained from the study conducted, the lowest air quality levels are on weekdays in the industrial, and on weekend in the commercial area. However, the CO and O3 concentrations obtained for all areas are still below the Recommended Malaysian Air Quality Guidelines (RMG), i.e., below 30 ppm for CO and below 0.10 ppm for O3. Whereas the NO2 and SO2 concentrations detected have exceeded the RMG limits for NO2 (0.17 ppm) and SO2 (0.13 ppm) at certain hours on both weekday and weekend, especially during the peak hours. Even though the situation is still under control, however, the study proves that the air quality in Pasir Gudang should be monitored and could be improved. The data obtained should be beneficial to decision makers as far as planning for future industrial developments in the area is concerned.